2013
DOI: 10.1007/s10461-013-0556-3
|View full text |Cite|
|
Sign up to set email alerts
|

Affected by HIV Stigma: Interpreting Results from a Population Survey of an Urban Center in Guangxi, China

Abstract: We aimed to identify factors related to HIV stigma in Liuzhou, Guangxi province, a city in southwest China with high HIV prevalence. We used a multi-stage cluster randomized sample of the general population to survey 852 adults. We conducted ordinal logistic regression analyses to test factors associated with punishment and isolation stigma. Eighteen percent of respondents agreed that people with HIV should be punished, and 40% agreed that people with HIV should be quarantined. Punishment stigma was associated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
8
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 39 publications
3
8
0
Order By: Relevance
“…Individuals were concerned not only of the effects of such stigma and discrimination on themselves, but also on their family members. These reported experiences and fears of HIV-associated stigma are consistent with several previous studies of HIV in China (1,14,15,25), including two in this issue (2,3). Similar to data reported in other recent research about PLHIV in China (1,2,4,14,15,2225,44–46), participants in this study described experiencing serious stigma from a broad range of sources: family, neighbors, health professionals, including doctors, and other people in the community.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Individuals were concerned not only of the effects of such stigma and discrimination on themselves, but also on their family members. These reported experiences and fears of HIV-associated stigma are consistent with several previous studies of HIV in China (1,14,15,25), including two in this issue (2,3). Similar to data reported in other recent research about PLHIV in China (1,2,4,14,15,2225,44–46), participants in this study described experiencing serious stigma from a broad range of sources: family, neighbors, health professionals, including doctors, and other people in the community.…”
Section: Discussionsupporting
confidence: 90%
“…PLHIV perceived that the stigma they experienced was compounded by stigma associated with HIV-acquisition behaviors, such as intravenous drug use and sex work. Abler and colleagues documented the high level of stigma that exists in the general public in Liuzhou toward PLHIV (3). In Hua and colleagues’ study of 27 PLHIV in Liuzhou, the vast majority of participants were highly isolated, rejected, unemployed, and impoverished as a result of their disclosure of their diagnosis (2).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In China, HIV stigma can be manifested in the society (Abler et al, 2014). A recent study reported that about 40% of respondents from general population in the society agreed that PLHIV should be isolated and 18% of them agreed that PLHIV should be punished (Abler et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…A recent study reported that about 40% of respondents from general population in the society agreed that PLHIV should be isolated and 18% of them agreed that PLHIV should be punished (Abler et al, 2014). The majority of Chinese PLHIV feel stigmatized (Zhang et al, 2014).…”
Section: Introductionmentioning
confidence: 99%